Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To find the [tex]\( y \)[/tex]-intercept of the equation [tex]\( y = 6 \left( x - \frac{1}{2} \right) (x + 3) \)[/tex] in the [tex]\( xy \)[/tex]-plane, follow these steps:
1. Recall that the [tex]\( y \)[/tex]-intercept of a graph occurs where [tex]\( x = 0 \)[/tex].
2. Substitute [tex]\( x = 0 \)[/tex] into the given equation to determine the [tex]\( y \)[/tex]-value at this point.
[tex]\[ y = 6 \left( 0 - \frac{1}{2} \right) (0 + 3) \][/tex]
3. Simplify the expression inside the parentheses first:
[tex]\[ 0 - \frac{1}{2} = -\frac{1}{2} \][/tex]
[tex]\[ 0 + 3 = 3 \][/tex]
4. Now, substitute these simplified values back into the equation:
[tex]\[ y = 6 \left( -\frac{1}{2} \right) (3) \][/tex]
5. Multiply the terms together:
[tex]\[ y = 6 \cdot \left( -\frac{1}{2} \right) \cdot 3 \][/tex]
6. Perform the multiplication step-by-step:
[tex]\[ 6 \cdot -\frac{1}{2} = -3 \][/tex]
[tex]\[ -3 \cdot 3 = -9 \][/tex]
7. Thus, the [tex]\( y \)[/tex]-intercept is:
[tex]\[ y = -9 \][/tex]
Therefore, the [tex]\( y \)[/tex]-intercept of the graph of the equation [tex]\( y = 6 \left( x - \frac{1}{2} \right) (x + 3) \)[/tex] is [tex]\( -9 \)[/tex]. Thus, the correct answer is:
[tex]\[ \boxed{-9} \][/tex]
1. Recall that the [tex]\( y \)[/tex]-intercept of a graph occurs where [tex]\( x = 0 \)[/tex].
2. Substitute [tex]\( x = 0 \)[/tex] into the given equation to determine the [tex]\( y \)[/tex]-value at this point.
[tex]\[ y = 6 \left( 0 - \frac{1}{2} \right) (0 + 3) \][/tex]
3. Simplify the expression inside the parentheses first:
[tex]\[ 0 - \frac{1}{2} = -\frac{1}{2} \][/tex]
[tex]\[ 0 + 3 = 3 \][/tex]
4. Now, substitute these simplified values back into the equation:
[tex]\[ y = 6 \left( -\frac{1}{2} \right) (3) \][/tex]
5. Multiply the terms together:
[tex]\[ y = 6 \cdot \left( -\frac{1}{2} \right) \cdot 3 \][/tex]
6. Perform the multiplication step-by-step:
[tex]\[ 6 \cdot -\frac{1}{2} = -3 \][/tex]
[tex]\[ -3 \cdot 3 = -9 \][/tex]
7. Thus, the [tex]\( y \)[/tex]-intercept is:
[tex]\[ y = -9 \][/tex]
Therefore, the [tex]\( y \)[/tex]-intercept of the graph of the equation [tex]\( y = 6 \left( x - \frac{1}{2} \right) (x + 3) \)[/tex] is [tex]\( -9 \)[/tex]. Thus, the correct answer is:
[tex]\[ \boxed{-9} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.